Activation of the oncogenic transcription factor B-Myb via multisite phosphorylation and prolyl cis/trans isomerization. Issue 1 (13th October 2018) - Werwein, Eugen; Cibis, Hannah; Hess, Daniel; Klempnauer, Karl-Heinz
Abstract: The oncogenic transcription factor B-Myb is an essential regulator of late cell cycle genes whose activation by phosphorylation is still poorly understood. We describe a stepwise phosphorylation mechanism of B-Myb, which involves sequential phosphorylations mediated by cyclin-dependent kinase (Cdk) and Polo-like kinase 1 (Plk1) and Pin1-facilitated peptidyl-prolyl cis/trans isomerization. Our data suggest a model in which initial Cdk-dependent phosphorylation of B-Myb enables subsequent Pin1 binding and Pin1-induced conformational changes of B-Myb. This, in turn, initiates further phosphorylation of Cdk-phosphosites, enabling Plk1 docking and subsequent Plk1-mediated phosphorylation of B-Myb to finally allow B-Myb to stimulate transcription of late cell cycle genes. Our observations reveal novel mechanistic hierarchies of B-Myb phosphorylation and activation and uncover regulatory principles that might also apply to other Myb family members. Strikingly, overexpression of B-Myb and of factors mediating its activation strongly correlates with adverse prognoses for tumor patients, emphasizing B-Myb's role in tumorigenesis.